Patterned superhydrophobic surfaces to process and characterize biomaterials and 3D cell culture. Issue 3 (21st March 2018) - Neto, A. I.; Levkin, P. A.; Mano, J. F.
Abstract : Microarrays are a technological breakthrough for high-throughput screening of large numbers of assays. Abstract : Microarrays are a technological breakthrough for high-throughput screening of large numbers of assays. We review the evolution of microarray platforms for 3D cell culture to exhibit complex biological environments for tissue engineering, diagnostics and disease models. Patterned microarrays with extreme wettabilities were suggested as a versatile platform for high-throughput assays to generate 3D cell environments, as well as to characterize and analyze biomaterials' properties and cell–cell and cell–biomaterial interactions. Among the emerging HTS approaches, platforms with extreme wettabilities have the potential to revolutionize biomedical research, offering opportunities for drug screening on 3D cell based-systems with high reproducibility, versatility and spatial control.